Development of medical devices: advantages of a methodic approach - Isa C.T. Santos (2011)
It is possible to advocate that, as far as complexity is concerned, the medical devices sector is comparable to the aviation and nuclear industries. Some of the arguments used are the broad definition of the term "medical device", the multiplicity of regulations and the nature of the relation between manufacturers and users. In such environment, the uncertainty associated to the development of novel devices is high and justifies the use of dedicated methodologies. In general, the application of product development methodologies helps to reduce the duration of the tasks, optimize the available resources and obtain products and/or services that please customers. In the case of medical devices, the authors believe that resorting to such methodologies is crucial to overcome the industry's complexity without losing competitiveness. The product development process involves the following steps: identification of an opportunity, voice of the customer, concept development, design, test and validation and launch. This paper describes each one of the aforementioned stages and suggests adaptations to the healthcare sector. Â(c) 2011 Springer-Verlag Berlin Heidelberg.